The Importance of Contrastive Approach in Teaching a Foreign Language – an Example of the Acquisition of Croatian by Polish Speakers - Kodrić, Ana; Vidović Bolt, Ivana (Poznańskie Studia Slawistyczne, 2013)
This paper describes the experience of working with a homogeneous group of students, ages 18–25 years old, who studied Croatian as a first or a second foreign Slavic language. A few, isolated examples showcase analysis of errors recorded or documented in tests, dictations, and essays as well as oral and written communication with Polish students of Croatian language. The errors are mistakes that reflect interference, the similarities between the two languages. Given the limited space in this paper, we will not offer strategies or tips to avoid these mistakes effectively.